2013
DOI: 10.1038/leu.2013.27
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Notch treatment prevents multiple myeloma cells localization to the bone marrow via the chemokine system CXCR4/SDF-1

Abstract: Multiple myeloma (MM) is a deadly hematopoietic malignancy characterized by proliferation of malignant plasma cells in the bone marrow (BM) and bone disease. Interactions between myeloma and BM cells facilitate tumor progression and resistance to therapies. CXCR4 and its ligand Stromal cell-derived factor-1 (SDF-1) have a primary role in this process and are associated with poor prognosis. The Notch pathway is active in myeloma cells, resulting in increased proliferation, resistance to apoptosis and osteolytic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
93
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 54 publications
5
93
0
Order By: Relevance
“…In contrast, a definite role for Notch pathway in the development of AML is less clear. Chiaramonte reported that Notch pathway was not activated in AML [13]. Similarly, Kannan and Lobry reported that Notch was silenced in AML [6,7].…”
Section: Discussionmentioning
confidence: 94%
“…In contrast, a definite role for Notch pathway in the development of AML is less clear. Chiaramonte reported that Notch pathway was not activated in AML [13]. Similarly, Kannan and Lobry reported that Notch was silenced in AML [6,7].…”
Section: Discussionmentioning
confidence: 94%
“…Aberrations in Notch signaling have also been linked to several hematological malignancies, including T-cell acute lymphoblastic leukemia (T-ALL), acute myeloid leukemia (AML), lymphoma and multiple myeloma (MM) [6,12]. The role of Notch signaling in hematopoiesis and in hematopoietic SC (HSC) development and maintenance has been extensively reviewed by Bigas and Espinosa [30], the fundamental finding being that activation of the Notch pathway is necessary for HSCs maintenance, and its inhibition results in HSCs differentiation and depletion [31].…”
Section: Notch and Ticsmentioning
confidence: 99%
“…Notch signaling is dependent on cell-to-cell communication and is activated when Notch ligands, present on the "sending cell", bind to Notch receptor on the "receiving cell". MyoD in myogenesis and E2A in B lymphopoiesis), the pre-TCR alpha (which participates in regulating the T cell progenitors differentiation), cell cycle regulatory genes such as cyclin D2, cyclin D1, p21 and p27, and genes from different chemokine systems [11,12,13].…”
Section: The Notch Pathwaymentioning
confidence: 99%
“…1,23 Notch signaling has been involved in the regulation of the expression and function of the CXCR4/SDF1 chemokine axis crucial for MM cell growth, survival, and migration. 24 Jagged2 increased the release of interleukin 6, vascular endothelial growth factor (VEGF), and insulin-growth factor 1 from BM stroma, factors known to promote MM cell survival, growth, and BM angiogenesis. 21 Notch signaling has been also implicated in the development of MM-associated bone disease, primarily through the stimulation of osteoclastogenesis.…”
Section: Introductionmentioning
confidence: 99%